Toluene oxidation by non-thermal plasma combined with palladium catalysts - Magureanu, Monica; Dobrin, Daniela; Mandache, Nicolae B.; Cojocaru, Bogdan; Parvulescu, Vasile I. (Frontiers in Chemistry, 2013)
The oxidation of toluene in air was investigated using a dielectric barrier discharge (DBD) combined with a Pd/Al2O3 catalyst. When using only plasma, rather low selectivity towards CO2 was obtained: 32-35%. By filling the DBD reactor with Pd/Al2O3 catalyst the CO2 selectivity was significantly enhanced (80-90%), however, a large amount of toluene was desorbed from the catalyst when the discharge was operated. By filling a quarter of the discharge gap with catalyst and placing the rest of the catalyst downstream of the plasma reactor, an important increase of CO2 selectivity (~75%) and a 15% increase in toluene conversion were achieved as compared to the results with plasma alone. The catalyst exhibited a very good stability in this reaction.